Juridical Review of the Crime of Illegal Logging in the Utilization of Private Forest Timber in the Perspective of Law Number 18 of 2013 Concerning the Prevention and Eradication of Forest Destruction - Fahrurazi Ammri; Dwi Putra Jaya; Hurairah Hurairah (Fakultas Hukum Dehasen, 2023)
The purpose of this study was to determine the regulation on the utilization of private forest timber and the category of illegal logging acts. This type of research is normative research and the research approach is a statutory approach. The primary source of legal material is statutory regulations. The results of the research show that the regulation on the use of private forest wood based on Law 41 of 1999 concerning Godhead and Law Number 18 of 2013 concerning Prevention and Eradication of Forest Destruction and Minister of Forestry Regulation Number 30 of 2012 concerning Administration of Forest Products Derived from Private Forests can work. together. For evidence of the legality of utilization of private forest, the two laws still refer to the Regulation of the Minister of Forestry Number 30 of 2012 concerning Administration of Forest Products Derived from Private Forests. Categories of illegal logging crimes in the utilization of private forest wood:(a) the use of a document of Transport Note or Self-Use Transport Note or SKAU which is proven to be used as a document for transporting timber originating from state forest areas, (b) if the legitimacy of the origin of private forest products cannot be proven. The conclusion is that it is a crime to exploit private forest wood, if evidence of land legality cannot be proven based on the Minister of Forestry Regulation Number 30 of 2012 concerning Administration of Forest Products Derived from Private Forests.